Cercopoidea types (Hemiptera-Cicadomorpha) housed at the Museo de la Plata entomological collection (Argentina) - Foieri, Alvaro; Marino de Remes Lenicov, Ana Maria (Museu de Zoologia da Universidade de São Paulo, 2025)
Type material of 11 species from seven genera of Cercopoidea is housed at the Entomology Division of the Facultad de Ciencias Naturales y Museo, Universidad Nacional de La Plata. The types listed herein correspond to species described by C. Berg (10 spp.) and Lallemand (1 sp.). The collection contains 24 type specimens. Lectotype and paralectotypes of Deois (Deois) knoblauchii (Berg), Kanaima katzensteinii (Berg), Mahanarva (Ipiranga) aguirrei (Berg), Tomaspis argentina Berg [= Deois terrea (Germar)], T. perezii Berg [= Deois terrea (Germar)] and T. platensis Berg are designated. Comparison of their original descriptions with the label information supports the existence of 2 holotypes, 6 lectotypes, 10 paralectotypes and 6 syntypes. The following information is given for each species: original species names, taxonomic catalogue, bibliographic references, type category, number of specimens, gender, Museo de La Plata code numbers, and transcription of data from labels (country, province, locality, date of collection, collector’s name, and hosts). Information about subsequent nomenclatural changes with corresponding references, the state of preservation of the specimens in each series and pictures of each species are also provided.